Magnetically geared induction machines - Mezani, S.; Hamiti, Tahar; Belguerras, L.; Lubin, T.; Rashed, Mohamed; Gerada, C. (IEEE, 2015)
A wound-rotor induction machine is artfully coupled to a magnetic gear to achieve a high-torque-density drive system called magnetically geared induction machine (MaGIM). The high-speed rotor of MaGIM is common to both the machine and gear sides. A rotating diode rectifier electrically links the machine's wound rotor and a dc boost winding on the gear side to increase the torque-transmission capabilities of the overall system. The first investigations on a 100 kW-120 r/min MaGIM are promising, since an increase in torque of ∼ 15% could be obtained by inserting the diode rectifier. For fixed speed applications, this induction-machine-based system can be directly supplied from the mains